The Diagnosis and treatment of subacute thyroiditis - a review of the literature - Marlena Cąkała; Magdalena Kozioł; Kamila Podgórniak; Aleksandra Zajkowska; Joanna Skotnicka; Maria Witkowska; Michał Szymchel; Filip Grzegorzak (Nicolaus Copernicus University in Toruń, 2024)
Introduction:  Subacute thyroiditis (SAT) is an inflammatory condition of the thyroid with characteristic presentations and clinical courses. The pathogenesis and determinants of the clinical course were unclear for many decades. The last few years have brought many clinically significant new data on the epidemiology, pathogenesis and management of subacute thyroiditis. The diagnosis is based on clinical presentation, laboratory tests (ESR, TSH, antithyroid antibodies), imaging tests (thyroid ultrasound, thyroid scintigraphy) and cytological tests. Taking into account all the new aspects of subacute thyroiditis pathogenesis and of its clinical course, the new - modified - criteria of subacute thyroiditis diagnosis have been proposed. Aim of the study: In this review, we provide a comprehensive overview of the current knowledge regarding subacute thyroiditis, including its epidemiology, pathophysiology, diagnostic methods, and the existing treatment options. Brief description of the state of knowledge: Many cases of subacute thyroiditis follow an upper respiratory viral illness, which is thought to trigger an inflammatory destruction of thyroid follicles. In most cases, the thyroid gland spontaneously resumes normal thyroid hormone production after several months. The most characteristic laboratory finding is a high erythrocyte sedimentation rate (ESR). C-reactive protein and white blood count (WBC) are also elevated in many cases. Anti-thyroid antibodies are believed to be usually normal. The ultrasound (US) pattern of subacute thyroiditis includes hypoechoic and heterogeneous areas with blurred margins, poorly vascularized on color Doppler. Treatment with high-dose acetylsalicylic acid or nonsteroidal anti-inflammatory drugs is directed toward relief of thyroid pain. It has been noticed that patients with a diagnosis of subacute thyroiditis visit more other clinics and receive antibiotics unnecessarily.